Technique of Stepwise Intracranial Decompression Combined with External Ventricular Drainage Catheters Improves the Prognosis of Acute Post-Traumatic Cerebral Hemispheric Brain Swelling Patients - Shi, Lei; Sun, Guan; Qian, Chunfa; Pan, Tianhong; Li, Xiaoliang; Zhang, Shuguang; Wang, Zhimin (Frontiers in Human Neuroscience, 2015)
Background: Acute post-traumatic cerebral hemispheric brain swelling (ACHS) is a serious disorder that occurs after traumatic brain injury (TBI), and it often requires immediate treatment. The aim of our clinical study was to assess the effects of stepwise intracranial decompression combined with external ventricular drainage catheters on the prognosis of ACHS patients. Methods: A retrospective study was performed on 172 cases of severe craniocerebral trauma patients with acute cerebral hemispheric swelling. The patients were divided into two groups: unilateral stepwise standard large trauma craniectomy (S-SLTC) combined with external ventricular drainage (EVD) catheter implants (n = 86) and unilateral routine frontal temporal parietal SLTC (control group, n = 86). Result: No significant differences in age, sex, or preoperative Glasgow Coma Scale score were observed between groups (P < 0.05). There were no significant differences in the ipsilateral subdural effusion incidence rates between the S-SLTC+EVD treatment group and the routine SLTC group. However, the incidence rates of intraoperative acute encephalocele and contralateral epidural and subdural hematoma in the S-SLTC+EVD group were significantly lower than those in the SLTC group (17.4% and 3.5% vs. 37.2% and 23.3%, respectively). The mean intracranial pressure (ICP) values of patients in the S-SLTC+EVD group were also lower than those in the SLTC group at days 1 through7 (P<0.05). A positive neurological outcome (GOS score 4 to 5, 50.0%) and decreased mortality (15.1%) was observed in the S-SLTC+EVD group compared to the neurological outcome (GOS score 4 to 5, 33.8%; 36.0%) in the SLTC group (P<0.05). Conclusions: Our data suggest that S-SLTC+EVD is more effective for controlling ICP, improving neurological outcome, and decreasing mortality rate compared with routine SLTC.